Accidents caused by venomous animals in the Northeast region of Brazil: Epidemiological profile of the last five years (Research, Society and Development, 2025)
The study aimed to analyze the epidemiological profile of accidents caused by venomous animals in the Northeast region of Brazil between 2018 and 2022. It is a descriptive, retrospective study with a quantitative approach, using data from the Notifiable Diseases Information System (SINAN), accessed through DATASUS. Sociodemographic and clinical variables were analyzed, such as age group, gender, type of animal involved, time to medical care, and case outcomes. The results showed 475,409 notifications during the period, with highlights for the states of Bahia (27.25%) and Pernambuco (22.28%), while Sergipe had the lowest number of records (2.67%). The highest incidence occurred among adults aged 20 to 59 years and in rural areas, often associated with agricultural activities. Scorpions accounted for most cases (62.63%), followed by snakes and bees, with variations between states. Most victims received care within three hours, with Alagoas standing out for the best indicators. Seasonality was observed, with peaks during warmer and rainy months. Most cases were classified as mild (83.19%), and the predominant outcome was recovery (87.36%). It is concluded that accidents involving venomous animals in the Northeast region are influenced by climatic, socioeconomic, and environmental factors. The implementation of public policies focused on prevention, health education, and improved access to medical care is essential to reduce morbidity and mortality associated with these accidents.